Information Seeking in Academic Research: A Study of the Sociology Faculty at the University of Wisconsin-Madison - Shen, Yi (Information Technology and Libraries, 2007)
This study examines how social scientists arrive at and utilize information in the course of their research. Results are drawn about the use of information resources and channels to address information inquiry, the strategies for information seeking, and the difficulties encountered in information seeking for academic research in today’s information environment. These findings refine the understanding of the dynamic relationship between information systems and services and their users within social-scientific research practice and provide implications for scholarly information-system development